Power losses in spiral bevel gears - Webb, Thomas Andrew. (2010)
This dissertation describes a numerical modelling strategy for characterising the windage of a spiral bevel gear rotating within a static shroud. The techniques employed include the use of a parametric solid model, and flow field modelling using computational fluid dynamics (CFD) software. A number of hypothetical physical alterations are made to a control system consisting of a gear and a shroud, based on those found in a Rolls-Royce aero engine.